The Well-Being of Children Living with Interethnic Parents: Are They at a Disadvantage? - Pearce-Morris, Jennifer (2012)
An increasing number of U.S. children are living with interethnic parents, yet we know relatively little about how they are faring. Using data from the first wave (1987–1988) of the National Survey of Families and Households (NSFH), this study examines differences in child well-being between children living with interethnic parents and those living with same-ethnic parents. Results provide only limited evidence that child well-being is lower among children living with interethnic parents. Compared with children in same-ethnic families, children living with interethnic parents exhibited higher levels of negative affect, and this difference could not be explained by differences in background or family characteristics, levels of parents relationship stressors, or parenting quality. At the same time, however, no differences were found in global well-being, positive affect, or behavior problems. Children living with interethnic parents may face some greater difficulties that warrant concern, but they do not appear to face pervasive disadvantages.